Um estudo sintático-semântico das preposições em complementos verbais de webjornais paulistas - Berto, Carine de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The main goal of this work is to evaluate the realization of the linguistic phenomenon of preposition and also to investigate how current normative pressures influence the production and the perception of processes of variation and change in Brazilian Portuguese. We analyze the use of prepositions a and para in verbal complementation contexts in contemporary journalistic texts from São Paulo’s press – the web newspapers. The contexts considered are constructions with complements of direction, movement with transference, material transference, and verbal/perceptual predicators (Berlinck, 1996; Corrêa, Cançado, 2006). Because written texts tend to be more conservative (i.e. more normative) this research provides an important linguistic investigation that contributes to the sociolinguistic knowledge of the language. However, the newspapers also tend to reflect the use, so they constitute a privileged place for us to understand the conflicting relationship between ‘norm’ and ‘use’. Besides this, the research is relevant for General Linguistics for considering linguistic and extralinguistic factors which determine the use and frequency of the prepositions, like syntactic-semantic relations between the preposition, the verb, the complement, and the text genre. We collected data from web newspapers from Araraquara, with small and medium circulation. Based on previous results, we have ascertained the predominance of the use of the preposition a in the newspapers from São Paulo in the 20th century. However, we have also ascertained representative records of variation... (Complete abstract click electronic access below)

Este trabalho tem por objetivo principal avaliar a realização do fenômeno linguístico da preposição, como também, investigar em que medida as pressões normativas vigentes influenciam na produção e percepção dos processos de variação e mudança do português brasileiro. Analisamos o emprego de preposições em contextos de complementação verbal em textos jornalísticos contemporâneos da imprensa paulista – os webjornais. Foi analisado o emprego das preposições a e para em construções com complementos de predicadores de direção, movimento com transferência, transferência material e transferência verbal/perceptual (Berlinck, 1996; Corrêa, Cançado, 2006). A pesquisa propicia uma investigação linguística importante para o conhecimento sócio-histórico da língua, já que o texto escrito possui uma tendência conservadora (o que o torna mais “normativo”); contudo, o jornal tende a refletir tendências de uso, sendo, por isso, um espaço privilegiado para entendermos o conflituoso jogo entre ‘norma’ e ‘uso’. Além disso, a pesquisa possui relevância para a Linguística Geral, por levar em consideração os fatores linguísticos e extralinguísticos que determinam o uso e a frequência das preposições, tais como as relações sintático-semânticas entre a preposição, o verbo, o complemento e o gênero textual. O material coletado se compõe de dados recolhidos com base em webjornais de circulação média e pequena da cidade de Araraquara. Com base em resultados anteriores que embasaram este trabalho, notamos que há nos jornais paulistas do século XX maior predominância do uso da preposição a. Porém, constatamos registros representativos de variação em empregos da preposição para em contextos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Lingua portuguesa - Verbos; Jornais eletrônicos; Lingua portuguesa - Preposições; Língua portuguesa - Analise sintatica